Comparison of Social Media Marketing Engagement Rates on My Rise (MSMEs) Salatiga - Deva Nita Mulya; Aldian Umbu Tamu Ama; Yashinta Putri Dwi Astuti; Galih Prasadhya (Jurnal Mantik, 2022)
The development of technology affects all aspects or fields, one of which is the field of business marketing which is often referred to as digital marketing. Digital marketing is currently the focus of business people, including MSMEs. They must quickly adapt to changes because it can help disseminate products to the public and increase sales. Business actors are facilitated by digital marketing platforms, such as social media, with various derivatives. This study aims to analyze the comparison of the level of engagement in social media marketing to the increase in sales and productivity of My Rise (MSMEs). The research method used in this study is qualitative. This research focuses on the level of engagement of each social media marketing used by My Rise. Through the data collection method through interviews and social media observations, the results of the research showed that the social media marketing used by My Rise is Instagram, Facebook, and TikTok, where each social media has its advantages in its use. However, the social media with the highest engagement is Instagram because more people use Instagram social media, so the target market is more targeted.